The Debate on Waqf (Signs of Stopping) at the Finishing End of Quran Verses | جدَلِية الوقوف على آواخر الآيات القرآنية - Mhamed Rebba; Zainuddin Bin Musa (Al-Zahra : Journal for Islamic and Arabic Studies, 2019)
In this paper, we deal with an important and scientific issue in the science of waqf (stop) and ibtidaa (beginning). The scholars differed about the waqf on the head of each verse of the Holy Quran, and there were so many various views and ambiguities about them. Looking at the whole mechanism of evidence, the Sunnah have different interpretations from what others said in other madhabs depending on the purposes of the Quranic stand. These two different groups identified their reasons for the Quranic stand depending on the intense message and how the reader recites the Holy Quran. This paper aims to reveal the different arguments made by these two groups and discuss them. Also to make the right decisions in order to reach correct statement on this issue.